Status of experimental knowledge on the unbound nucleus 13Be - Jones, K. L.; Kovoor, J.; Kanungo, R. (Frontiers in Physics, 2023)
The structure of the unbound nucleus 13Be is important to understanding the Borromean, two neutron halo nucleus 14Be. The experimental studies conducted over the last four decades are reviewed in the context of the beryllium chain of isotopes and some significant theoretical studies. One focus of this paper is the comparison of new data from a 12Be(d,p) reaction in inverse kinematics, which was analyzed using GEANT4 simulations and a Bayesian fitting procedure, with previous measurements Kovoor et al. (2023). Two possible scenarios to explain the strength below 1 MeV above the neutron separation energy were proposed in that study: a single p-wave resonance, or a mixture of an s-wave virtual state with a weaker either p-wave or d-wave resonance. Comparisons of recent invariant mass and the (d,p) experiments show good agreement between the transfer measurement and the high-energy nucleon removal measurements of Corsi et al. (2019) and Ribeiro et al. (2018).